Digital Transformation and its Impact on the Quality of Accounting Information in Financial Statements - Amal Issa Saleh; Wael Sassi Mohamed Adheim (Journal of Scientific and Human Dimensions, 2026)
This study aims to analyze the impact of digital transformation on the quality of accounting information in commercial banks, through a field study applied to the Commercial Bank in Tobruk. The study is based on the hypothesis that adopting digital transformation applications contributes to improving the qualitative characteristics of accounting information, thereby supporting the efficiency of financial and administrative decisions within banking institutions. The study adopted the descriptive analytical method and used the questionnaire as the main tool for data collection. A total of (40) questionnaires were distributed to employees of the Commercial Bank (the Main Branch and Dar es Salaam Branch) in Tobruk. The data were analyzed using appropriate statistical methods to test the study’s hypotheses and measure the impact of digital transformation on the quality of accounting information. The study focused on the qualitative characteristics of accounting information, namely relevance, reliability, understandability, comparability, and timeliness. The results showed a statistically significant impact of digital transformation on the quality of accounting information in commercial banks, as it contributed to improving the accuracy of information, accelerating the preparation of financial reports, and enhancing its reliability and relevance for its users. This study contributes to enriching the accounting literature related to digital transformation in the banking environment, particularly in the Libyan context. It also recommends strengthening investment in digital infrastructure and developing human resource competencies to ensure sustainable improvement in the quality of accounting information.